(untitled) (Confluenţe Bibliologice, 2017)
Is presented the report of the librarians activities of the USARB Science Library during the Open Education Week. During this week, were promoted meetings with students from different faculties, were presented book exhibitions from the SL USARB collection, both traditional and online.